Assessment of Nurses – Midwives Practices Regarding Prolonged Labor in Babylon Governorate - Homadi, saadia; ali, Rabia (Iraqi National Journal of Nursing Specialties, 2005)
Objective : to assess the nurse-midwives practices regarding prolonging labor in Babylon Governorate hospitals . Methodology : Purposive sample of (57) nurse-midwives, which was selected from (6) hospitals included (3) General Hospital, (2) Maternity Hospital and Teaching Hospital .These nurse-midwives represented several nursing educational levels. A questionnaire was constructed for the purpose of the study, which was comprised demographic characteristics, information a bout nurse-midwives related to their ages, marital status, educational level, experience years in nursing and delivery , and attending midwifery courses through out their work . Results :The study findings indicated that , there were a significant relation ship between the nurse-midwives practices regarding prolonged labor and their ages (x2 = 23.434. P